Tools and techniques for implementing international e-trading tactics for competitive advantage - Meral, Yurdagül (IGI Global, 2019)
The use of ICT applications has dipped into almost every aspect of the business sector, including trade. With the volume of e-commerce increasing, international traders must switch their rules and practices to e-trade to survive in such a competitive market. However, the complexity of international trade, which covers customs processes, different legislation, specific documentation requirements, different languages, different currencies, and different payment systems and risk, presents its own challenges in this transition. Tools and Techniques for Implementing International E-Trading Tactics for Competitive Advantage examines the multidisciplinary approach of international e-trade as it applies to information technology, digital marketing, digital communication, online reputation management, and different legislation and risks. The content within this publication examines digital advertising, consumer behavior, and e-commerce and is designed for international traders, entrepreneurs, business professionals, researchers, academicians, and students.
Keywords: İnternational; Competitive Advantage; Tools and Techniques